Tri Hita Karana-Based Governance and Financial Performance of Village Credit Institutions (LPDs): Moderating Effects of Location and IT - Made Gede Wirakusuma; I Made Mertha (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
Village Credit Institutions (Lembaga Perkreditan Desa/LPDs) in Bali play a strategic role in community-based financial empowerment, yet many face governance and performance challenges. This study aims to examine the effect of Tri Hita Karana (THK)-based governance on the financial performance of LPDs and to test whether institutional fundamentals, specifically location and information technology adoption, moderate this relationship. Using legitimacy theory as the underlying framework, this quantitative research employed data from 94 LPDs across nine regencies in Bali, analyzed through Moderated Regression Analysis (MRA). The results indicate that THK-based governance has a positive and significant effect on financial performance (? = 0.412, p 0.05). Furthermore, both location (? = 0.217, p 0.05) and information technology adoption (? = 0.294, p 0.05) strengthen the relationship between governance and performance. These findings demonstrate that the integration of cultural ethics and digital transformation enhances institutional accountability and sustainability. The study contributes theoretically by extending good corporate governance (GCG) through cultural and technological perspectives and offers practical insights for policymakers to reinforce THK-based governance in LPDs